High Quality Vocational Programs: A Solution for Alleviating Acute Poverty and Achieving 8% Economic Growth Amid Indonesia's Demographic Bonus - Setiawan, R. Beniadi (CV. Green Publisher Indonesia, 2025)
Indonesia's demographic bonus presents a significant opportunity to accelerate economic growth, but without proper workforce development, it may lead to rising unemployment and poverty. High-quality vocational programs equip individuals with industry-relevant skills, ensuring better job absorption and entrepreneurial opportunities. Strengthening vocational education through policy support, industry collaboration, and curriculum enhancement is essential to achieving sustainable economic growth and poverty alleviation. This study analyzes how high-quality vocational programs can enhance workforce skills, reduce unemployment rates, and contribute to sustainable economic growth. This study employs a descriptive method with a qualitative approach to analyze the effectiveness of vocational programs in alleviating poverty and promoting economic growth. Data is collected through literature studies and observations of vocational program implementation in various regions of Indonesia. The data analysis follows Miles and Huberman's interactive model, which includes data reduction, data presentation, and conclusion drawing to understand the patterns and effectiveness of vocational policies on societal economic well-being. The research findings indicate that high-quality vocational programs significantly reduce acute poverty by equipping the workforce with industry-relevant skills, leading to higher employability and income stability. Additionally, vocational education aligned with industry needs enhances national productivity, supporting Indonesia's goal of achieving 8% economic growth amid the demographic bonus. Effective implementation requires strong collaboration between the government, industry stakeholders such as Kadin Indonesia, and educational institutions to ensure accreditation, certification, and quality assurance of vocational training programs.